2014
DOI: 10.1186/1471-2458-14-1014
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal mortality by place of delivery in sub-Saharan Africa: a meta-analysis of population-based cohort studies

Abstract: BackgroundFacility-based delivery has gained traction as a key strategy for reducing maternal and perinatal mortality in developing countries. However, robust evidence of impact of place of delivery on maternal and perinatal mortality is lacking. We aimed to estimate the risk of maternal and perinatal mortality by place of delivery in sub-Saharan Africa.MethodsWe conducted a systematic review of population-based cohort studies reporting on risk of maternal or perinatal mortality at the individual level by plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 52 publications
6
86
0
3
Order By: Relevance
“…However, this result is in line with similar studies conducted in Nigeria [31] and Malawi and Zambia [39] but in contrast with studies conducted n LMICs, [32] Bangladesh, [33] Indonesia, [34] Tanzania [35] and SSA. [36] Children of mothers aged 25-49 years were found to be significantly associated with increased risk of child mortality. This could be due to the non-utilization of maternal and child health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this result is in line with similar studies conducted in Nigeria [31] and Malawi and Zambia [39] but in contrast with studies conducted n LMICs, [32] Bangladesh, [33] Indonesia, [34] Tanzania [35] and SSA. [36] Children of mothers aged 25-49 years were found to be significantly associated with increased risk of child mortality. This could be due to the non-utilization of maternal and child health services.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Studies conducted on the impact of health facility-based delivery on child mortality elsewhere have shown that health facility-based delivery reduce the risk of child mortality. [32,33,34,35,36] Hence, the need for a study focusing on health facility-based delivery as the main predictor variable of child mortality in Nigeria to generate new knowledge on how best to address the problem of child survival. This study aims to examine the relationship between health facility-based delivery and child mortality in Nigeria.…”
Section: American Journal Of Public Health Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this risk, more than 67% of Zambian women in rural areas deliver at home [1]. Home delivery is assumed to be a maternal mortality risk, because of its positive association with maternal mortality [3] (although more recent research is needed [4]) and the negative association between skilled assistance at birth and maternal mortality [5]. Although safe motherhood strategies [5] do not preclude home delivery, fewer than 50% of births in Zambia are attended to by a skilled assistant [6], implying that home delivery remains riskier.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, this study will not assess neonatal or maternal mortality at the community level. The attributable risk of death for neonates born at home compared to those born in health facilities in SSA is estimated to be 21% [53]. The DHIMS-2 database from which data for evaluation of the CRCT will be extracted is a web-based platform built on the District Health Information System-2 (DHIMS-2) open source software.…”
Section: Discussionmentioning
confidence: 99%